Dispelling the Myths of Percutaneous Catheter Drainage of Infected Abdominal Collections - Lorenz, Jonathan M. (Seminars in Interventional Radiology, 2024)
When consulted for percutaneous catheter drainage (PCD) of abdominopelvic collections, interventional radiologists (IRs) should consider the appropriateness of this technique in the context of other options such as conservative, endoscopic, or surgical management. Whenever possible, published data should be considered prior to performing percutaneous drainage, especially as regards controversial scenarios such as the use of fibrinolytic therapy, the primary placement of large-bore drainage catheters, the drainage of cystic tumors, the drainage of splenic abscesses, and the treatment of collections lacking an in-line drainage window. This article examines past and present published data on PCD to dispel some common myths and guide IRs toward the best applications of PCD.
Keywords: abdominal abscess drainage; percutaneous abscess drainage; cystic tumors drainage; splenic abscess drainage; interventional radiology